Circulating CD4⁺ CD25⁺ regulatory T cells correlate with chronic hepatitis B infection - Peng, Guoping; Li, Shuping; Wu, Wei; Sun, Zhen; Chen, Yiqiong; Chen, Zhi (Immunology, 2008)
Circulating CD4⁺ CD25⁺ regulatory T cells (Tregs) have been demonstrated to maintain immunotolerance and suppress the antigen-specific or antigen-non-specific T-cell responses, but their role in chronic hepatitis B (CHB) infection in humans has not been well characterized. In this study, we analysed the frequency and phenotypic characteristics of CD4⁺ CD25⁺ Tregs in patients of different hepatitis B virus (HBV) infection status, and investigated the effect of Tregs on antiviral immune responses in CHB patients, and the mechanism of this effect. A total of 137 subjects, including 79 CHB patients, 26 asymptomatic HBV carriers (ASCs), 12 acute hepatitis B (AHB) patients and 20 healthy controls, were enrolled in the study. We found that the frequency of CD4⁺ CD25high Tregs in AHB patients was comparable to that in healthy controls, while it was significantly increased in CHB patients. CD4⁺ CD25⁺ Tregs produced interleukin (IL)-10 but little or no interferon (IFN)-γ under anti-CD3 stimulation. In CHB patients, the frequency of CD4⁺ CD25high Tregs positively correlated with serum viral load, and the Tregs were capable of suppressing the proliferation and IFN-γ production of autologous peripheral blood mononuclear cells (PBMC) mediated by HBV antigen stimulation in vitro. However, combined administration of anti-programmed death-1 (PD-1) and anti-cytotoxic lymphocyte antigen-4 (CTLA-4) monoclonal antibody slightly enhanced the cellular proliferation and significantly increased the IFN-γ production of PBMC cocultured with Tregs at a ratio of 2 : 1. Thus, the frequency of circulating CD4⁺ CD25⁺ Tregs is increased in patients with CHB, and this may play an important role in viral persistence by modulating virus-specific immune responses.